The role of interleukin-6 trans-signalling on cardiovascular dysfunction in inflammatory arthritis. (11th December 2020) - Davies, Ruth; Williams, Jessica; Sime, Katie; Jin, Hyun-Sun; Thompson, Charlotte; Jordan, Lauren; Lang, Derek; Halcox, Julian P; Ellins, Elizabeth; Jones, Gareth W; Jones, Simon A; Rose-John, Stefan; et al.
Abstract: Objectives: Cardiovascular (CV) mortality in RA patients is 50% higher than in the general population. There is increasing recognition that systemic inflammation is a major driver of this. IL-6 is implicated in cardiovascular disease (CVD) in the general population but its role in CVD in RA is undefined. Of the two modes of IL-6 signalling, trans-signalling is pro-inflammatory whereas classical signalling is linked with inflammation resolution. This study examines the role of IL-6 trans-signalling in CVD in a mouse model and patients with RA. Methods: Myography determined the effect of IL-6 trans-signalling blockade, using sgp130Fc, on aortic constriction in murine collagen-induced arthritis. Serum CCL2 and sVCAM-1 as soluble biomarkers of sIL-6R trans-signalling were investigated in a human cross-sectional study. An observational longitudinal study investigated the association between these biomarkers and progression of subclinical atherosclerosis in early RA by measuring carotid intima-media thickness (CIMT). Results: sgp130Fc reduced arthritis severity, serum CCL2 and sVCAM-1 and restored vascular function in collagen-induced arthritis (CIA). In established RA, sVCAM-1 correlated with the 28-joint DAS (DAS28) and CV risk. In early RA, baseline DAS28 was associated with CIMT change at 6 months. CIMT 'rapid progressors' at 12 months had higher baseline sVCAM-1, haemoglobin A1c, cholesterol:high-density lipoprotein cholesterol ratio and LDL cholesterol. Conclusions: IL-6 trans-signalling plays a pivotal role in vascular dysfunction in CIA. In early RA, sVCAM-1 was associated with progression of subclinical atherosclerosis. Inflammation from RA onset in CVD-susceptible individuals may accelerate atherosclerosis. IL-6 trans-signalling blockade may be beneficial to RA patients and perhaps for atherosclerosis in the general population.